Tax incentives in Polish pension system - Krzysztof Biernacki (Economic and Environmental Studies (E&ES), 2017)
Polish pension system has been severely changed in last years. However, it is still hard to find a purpose, for what these changes have been done. At the beginning of 1990 Polish pension system based on current payment (pass as you go system). In the end of 1998 a capital component was introduced. In the initial period of the mix system (pass as you go and capital) it was visible, that insured persons were not interested in self-building a capital for future pension payments. Due to this fact, special incentives were introduced. They were strictly associated with tax system, because these instruments introduced the possibility to minimize the tax base for those, who decided to save for own pension. This article analyses statistics dates concern these incentives and verifies the hypothesis, whether tax system shall create incentives for long-term saving plans.
Keywords: H24; H55; 330; pension system; tax system